NLR in eXile: Emerging roles of NLRX1 in immunity and human disease. Issue 3 (28th December 2020) - Pickering, Robert J.; Booty, Lee M.
Summary: NLRX1 is a member of the NOD‐like receptor family, a set of pattern recognition receptors associated with innate immunity. Interestingly, NLRX1 exists in somewhat of an exile from its NLR counterparts with unique features that mediate atypical functions compared with traditional NOD‐like receptors (NLRs). Aside from a mitochondrial targeting sequence, the N‐terminal region is yet to be characterized. Mitochondrially located, NLRX1 sits within a subgroup of regulatory NLRs responsible for negatively regulating cellular inflammatory signalling. As well as modulating pathogen response, emerging evidence is implicating NLRX1 as a central homeostatic gatekeeper between mitochondrial biology and immunological response. More recently, NLRX1 has been implicated in a wide range of disease, both pathogen‐driven and otherwise. Emerging links of NLRX1 in cancer biology, autoimmunity and other inflammatory conditions are raising the potential of targeting NLRX1 therapeutically, with recent studies in inflammatory bowel disease showing great promise. Within this review, we address the unique features of NLRX1, its roles in innate immune signalling and its involvement in a range of inflammatory, metabolic and oncology disease indications with a focus on areas that could benefit from therapeutic targeting of NLRX1. Abstract : NLRX1 is an underappreciated member of the NOD‐like receptor family. Functions in pathogen response are responsible for the regulation of multiple immune pathways. Emergence in disease highlights the potential in exploiting NLRX1 as a therapeutic target.